Streamlining Change Control Processes in Regulatory Affairs: Best Practices and Case Studies - Challa, Sri Sai Subramanyam; Chawda, Abhip Dilip; Benke, Abhishek Pandurang; Tilala, Mitul (Integrated Journal for Research in Arts and Humanities, 2024)
Change control is a critical component of regulatory affairs in various industries, particularly in pharmaceuticals, medical devices, and biotechnology. This research paper explores the challenges associated with traditional change control processes and presents best practices for streamlining these processes to improve efficiency, compliance, and overall product quality. Through a comprehensive literature review and analysis of case studies from leading organizations, we identify key strategies for optimizing change control workflows, leveraging technology, and fostering a culture of continuous improvement. The paper also examines the impact of streamlined change control processes on regulatory compliance, product lifecycle management, and organizational performance. Our findings suggest that implementing these best practices can lead to significant reductions in change implementation time, improved regulatory compliance, and enhanced product quality and safety.